2020
DOI: 10.3389/fonc.2020.01015
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression in Glioblastoma, the Clinical and Prognostic Significance: A Systematic Literature Review and Meta-Analysis

Abstract: Background: The clinical and prognostic value of programmed death-ligand 1, PD-L1, in glioblastoma remains controversial. The present study aimed to identify the expression of PD-L1 for its prognostic value in glioblastoma. Methods: A comprehensive literature search was performed using the PubMed and CNKI databases. The overall survival (OS) and disease-free survival (DFS) of GBM was analyzed based on Hazard ratios (HRs) and 95% confidence intervals (CIs). Furthermore, Odds ratios (ORs) and 95% CIs were summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 73 publications
3
52
0
1
Order By: Relevance
“…Our result also showed that NPC2 independently indicated unfavorable prognosis in glioma when adjusted for with patents’ age ( p value = 0.04) and alive status ( p value = 0.039) ( Table 1 ), which revealed that NPC2 was a robust independent factor for predicting GBM survival. Considering that age has been identified as prognostic factors for GBM ( Chen P. et al, 2020 ; Hao et al, 2020 ; Zheng et al, 2020 ), NPC2 might be a prognostic marker of GBM based on its significant positive correlation with this disease. Hence, we focus on investing the clinical prognostic significance of the NPC2 genes in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Our result also showed that NPC2 independently indicated unfavorable prognosis in glioma when adjusted for with patents’ age ( p value = 0.04) and alive status ( p value = 0.039) ( Table 1 ), which revealed that NPC2 was a robust independent factor for predicting GBM survival. Considering that age has been identified as prognostic factors for GBM ( Chen P. et al, 2020 ; Hao et al, 2020 ; Zheng et al, 2020 ), NPC2 might be a prognostic marker of GBM based on its significant positive correlation with this disease. Hence, we focus on investing the clinical prognostic significance of the NPC2 genes in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the intensity of PD-L1 occurrence corresponds with an effective response to ICIs related pathway [ 19 ]. A meta-analysis performed by Hao et al [ 20 ] analyzed 9 studies of adult PD-L1 positive glioblastoma patients [ 20 ], which suggested the high incidence of PD-L1 to be connected with poor patient survival. No differences were found between PD-L1 and gender as well as age, which was similar to results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that TMZ treatment differentially affects PD-L1 expression levels in different types of human GBM cells under different culture conditions. High expression of PD-L1 in GBM tumor tissues is associated with poor survival of patients [22]. Recent clinical trials have revealed a lower response of targeted PD-L1 immunotherapy in recurrent GBM [23].…”
Section: Discussionmentioning
confidence: 99%